Chain extender effect of 3-(4-hydroxyphenyl)propionic acid/layered double hydroxide in biopolyesters containing the succinate moiety. (2nd April 2020) - Sisti, Laura; Totaro, Grazia; Celli, Annamaria; Marek, Adam A.; Verney, Vincent; Leroux, Fabrice
Abstract : 3-(4-Hydroxyphenyl)propionic acid intercalated in Mg2 Al/layered double hydroxide has been used as a filler in biopolyesters containing the succinate moiety, with the aim of inducing a chain extender effect. Abstract : 3-(4-Hydroxyphenyl)propionic acid intercalated in Mg2 Al/layered double hydroxide has been used as a filler in biopolyesters containing the succinate moiety, such as poly(propylene succinate) (PPS), poly(butylene succinate- co -butylene adipate) (PBSA) and poly(butylene succinate) (PBS), with the aim of inducing an effect similar to that of an increment of the molecular weight of the matrices. The composites (1, 5 and 10 wt% of filler) have been prepared by a simple melt blending procedure. X-ray diffraction analysis revealed the presence of intercalated structures in the composites. From melt rheology measurements, a chain extender effect of the filler, towards PBS, PPS and to some extent PBSA, was evident and proportional to the composition, producing a reinforcing role of the filler towards the polymeric chains. Moreover, no gel-like structure was produced. Such findings can be useful in widening the processing window of biopolyesters, in order to design multifunctional materials with adapted properties.